A new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps - Namazi, Mehdi; Tavana, Madjid; Mohammadi, Emran; Bonyadi Naeini, Ali (Benchmarking: An International Journal)
Purpose New business practices and the globalization of markets force firms to take innovation as the fundamental pillar of their competitive strategy. Research and Development (R&D) plays a vital role in innovation. As technology advances and product life cycles become shorter, firms rely on R&D as a strategy to invigorate innovation. R&D project portfolio selection is a complex and challenging task. Despite the management's efforts to implement the best project portfolio selection practices, many projects continue to fail or miss their target. The problem is that selecting R&D projects requires a deep understanding of strategic vision and technical capabilities. However, many decision-makers lack technological insight or strategic vision. This article aims to provide a method to capitalize on the expertise of R&D professionals to assist managers in making informed and effective decisions. It also provides a framework for aligning the portfolio of R&D projects with the organizational vision and mission. Design/methodology/approach This article proposes a new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps. Findings The proposed strategy plane helps decision-makers align R&D project portfolios with their strategies to combine a strategic view and numerical analysis in this research. The proposed strategy plane consists of four areas: Exploitation Zone, Challenge Zone, Desperation Zone and Discretion Zone. Mapping the project into this strategic plane would help decision-makers align their project portfolio according to the corporate perspectives. Originality/value The new approach combines the efficiency and uncertainty dimensions in portfolio selection into an integrated framework that: (i) provides a complete representation of the stochastic decision-making processes, (ii) models the endogenous uncertainty inherent in the project selection process and (iii) proposes a computationally practical and visually unique solution procedure for classifying desirable and undesirable R&D projects.
Keywords: Business and International Management; Strategy and Management

Work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and their impact on cultural participation - Flath, Beate; Momen Pour Tafreshi, Maryam (Arts and the Market)
Purpose The purpose of this article is to illuminate the relations of work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and barriers and needs of vulnerable customers (VC) in order to explore possibilities to increase cultural participation of VC. Design/methodology/approach This article explores work-related practices of managers of live music events in OWL and asks if and to what extent these practices have an influence on the cultural participation of “vulnerable customers” (VC). It combines the findings of two studies: a) an explorative investigation on the work-related self-conceptions of managers of live music events in OWL (Study 1), and b) a sub-project on cultural participation of VC, which is part of the research project “kulturPreis. Increasing cultural participation through innovative and economically sustainable pricing concepts”, funded by the German Federal Ministry of Education and Research (Study 2). Findings It can be stated that there is an imbalance of knowledge: while VC tend to have a clear understanding of which barriers are the responsibility of managers of live music events, managers tend to lack knowledge regarding the needs of VC, and regarding the interrelationships between financial and social barriers facing them. Whether this knowledge and understanding can be developed in the future depends on the possibilities of exchanges between managers of live music events, cultural institutions, welfare organisations, political institutions and not least VC. Originality/value Based on these studies, this article combines different approaches by linking work-related practices of managers of live music events with cultural participation of VC.

Data Science und Big Data in der beruflichen Bildung – Konzeption und Erprobung eines Projektkurses für die Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael (Sammelband der 27. Fachtagung der BAG Berufliche Bildung)
Die Themen „Big Data“, „Künstliche Intelligenz und „Data Science“ werden seit einiger Zeit nicht nur in der breiten Öffentlichkeit kontrovers diskutiert, sondern stellen für die Ausbildung in den IT- und IT-nahen Berufen schon heute neue Herausforderungen dar, die in Zukunft durch die gesellschaftliche und technologische Weiterentwicklung hin zu einer Datengesellschaft noch größer werden. An dieser Stelle stellt sich die Frage, welche Aspekte dieses großen Themenkomplexes für Schule und Ausbildung von Wichtigkeit sind und wie diese Themen sinnstiftend und gewinnbringend in die informatische Ausbildung in verschiedenen Bildungsgängen integriert werden können. Im Rahmen des von uns im Jahr 2017 organisierten Symposiums zum Thema „Data Science“ wurden für die Bildung relevante Aspekte erörtert, wodurch als Kernelemente für den Unterricht Algorithmen der Künstlichen Intelligenz und ihre Anwendung in Industrie und Gesellschaft, Explorationen von Big Data sowie der Umgang mit eigenen Daten in sozialen Netzwerken herausgearbeitet wurden. Ziel ist, aus diesen Themenbereichen sowohl ein umfassendes Curriculum als auch Module für verschiedene Unterrichtsszenarien zu entwickeln und zu erproben. Durch diese Materialien soll es Lehrkräften aus der Informatik, Mathematik oder Technik ermöglicht werden, diese Themen auf Basis des Curriculums und der erprobten Unterrichtskonzepte selbst zu unterrichten. Hierfür wurde im Rahmen des Projekts ProDaBi (Projekt Data Science und Big Data in der Schule, https://www.prodabi.de), initiiert von der Telekom Stiftung, ein experimenteller Projektkurs entwickelt, den wir mit Schüler:innen der Sekundarstufe II an der Universität Paderborn im Schuljahr 2018/19 durchführten. Dieser Kurs enthält neben einem Modul zur Exploration von Big Data und einem weiteren Modul zum Maschinellen Lernen als Teil der Künstlichen Intelligenz auch eine Projektphase, die es in Zusammenarbeit mit lokalen Unternehmen den Schüler:innen ermöglicht, das Erlernte in ein reales Data Science-Projekt einzubringen. Aus den Erfahrungen dieses Projektkurses sowie den parallel durchgeführten Erprobungen einzelner Bausteine auch mit beruflichen Schulen werden ab dem Schuljahr 2019/20 die hierfür verwendeten Materialien weiterentwickelt und weiteren Kooperationspartnern zur Erprobung zur Verfügung gestellt. Damit wurden zum Ende des Projekts nicht nur vollständige Unterrichtsmaterialien, sondern auch ein umfassendes Curriculum entwickelt.
Keywords: Berufsbildung; vocational education; Ausbildung; training; berufliche Weiterbildung; advanced vocational education; Digitalisierung; digitalization; Unterricht; teaching; Lehrmethode; teaching method; Interdisziplinarität; interdisciplinarity; Fachdidaktik; subject didactics; Curriculum; curriculum; gewerblich-technischer Beruf; vocational/technical occupation; Fachkraft; specialist; Qualifikationsanforderungen; qualification requirements; Kompetenz; competence; Lehrerbildung; teacher training; Bundesrepublik Deutschland; Federal Republic of Germany

Video analysis in Design-Based Research – Findings of a project on self-organised learning at a vocational school - Gössling, Bernd; Daniel, Desiree (EDeR. Educational Design Research)
The use of video analysis in Design-Based Research (DBR) seems to be promising, because the quality of video data matches the reality of educational fields. Educational fields are multidimensional and complex. And more than other types of data, video may capture, for example, the simultaneity of verbal and non-verbal interactions. This seems to be valuable in the quest for new insights and better designs of educational interventions. However, to date there has been limited use of video data in researching their design. This paper aims at reflecting how the benefits of video-based analysis may be utilised in DBR. Experiences with the collection and analysis of video data in a project to design self-organised learning (SOL) at a vocational school in Germany will be used as a case study to illustrate the type of findings that may feed into the DBR process. In this case, the project school had already introduced a sophisticated SOL model but was experiencing various implementation difficulties. Resolving issues like this requires insights into how exactly a concept is realised and what happens in the field. Therefore, video data on classroom interactions was gathered and sub-sequently analysed using the documentary method. This led to the reconstruction of two different types of orientation that were guiding the students when they dealt with their self-organised learning environment. In a subversive orientation, students playfully infiltrate the formal learning space with peer activities. In a confirming orientation, students stick to both, the (informal) rules of the (formal) learning arrangement and of the peer environment, thus expressing respect for the boundary between these two worlds. These findings have been used to redesign the SOL intervention.
Keywords: Pulmonary and Respiratory Medicine; Pediatrics; Perinatology and Child Health

Time for Addressing Software Security Issues: Prediction Models and Impacting Factors - Ben Othmane, Lotfi; Chehrazi, Golriz; Bodden, Eric; Tsalovski, Petar; Brucker, Achim D. (Data Science and Engineering)
Finding and fixing software vulnerabilities have become a major struggle for most software development companies. While generally without alternative, such fixing efforts are a major cost factor, which is why companies have a vital interest in focusing their secure software development activities such that they obtain an optimal return on this investment. We investigate, in this paper, quantitatively the major factors that impact the time it takes to fix a given security issue based on data collected automatically within SAP's secure development process, and we show how the issue fix time could be used to monitor the fixing process. We use three machine learning methods and evaluate their predictive power in predicting the time to fix issues. Interestingly, the models indicate that vulnerability type has less dominant impact on issue fix time than previously believed. The time it takes to fix an issue instead seems much more related to the component in which the potential vulnerability resides, the project related to the issue, the development groups that address the issue, and the closeness of the software release date. This indicates that the software structure, the fixing processes, and the development groups are the dominant factors that impact the time spent to address security issues. SAP can use the models to implement a continuous improvement of its secure software development process and to measure the impact of individual improvements. The development teams at SAP develop different types of software, adopt different internal development processes, use different programming languages and platforms, and are located in different cities and countries. Other organizations, may use the results---with precaution---and be learning organizations.

Amsterdamer Publikationen zur Sprache und Literatur (Herausgebertätigkeit von Norbert Otto Eke von Bd. 158, 2005, bis Bd. 174, 2016)
Bd. 158: Rodney Taylor: Studies on Leibnitz in German Thought and Literature 1787-1835. Berlin: Weidler 2005. 260 S. Bd. 159: Jonathan Wooley: The Ethical Project in Rolf Dieter Brinkmann’s Westwärts 1&2. Berlin: Weidler 2005. 186 S. Bd. 160: Sara Smart: The Ideal Image: Studies in Writing fort he German Court 1616-1706. Berlin: Weidler 2005. S. 370 S. Bd. 161: Teresa Ludden: ‚Das Undarstellbare darstellen’: Kulturkritik and the Representation of Difference in the works of Anne Duden. Berlin: Weidler 2006. 267 S. Bd. 162: Frank Krause: Klangbewußter Expressionismus. Moderne Techniken des rituellen Ausdrucks. Berlin: Weidler 2006. 322 S. Bd. 163: Birgit Lang: Eine Fahrt ins Blaue. Deutschsprachiges Theater und Kabarett im australischen Exil und Nach-Exil (1933-1988). Berlin: Weidler 2006. 346 S. Bd. 164: Marielle Sutherland: Images of Absence: Death and the Language of Concealment in the Poetry of Rainer Maria Rilke. Berlin: Weidler 2006. 302 S. Bd. 165: Andreas Kramer: Regionalismus und Moderne. Studien zur deutschen Literatur 1900-1933. Berlin: Weidler 2006. 409 S. Bd. 166: Marc Oliver Huber: Zwischen Schlussstrich und „Schönem Gespräch“. Erinnerung bei Thomas Mann. Berlin: Weidler 2007. 275 S. Bd. 167: Gerd Labroisse: Politisch-Historisches in literarischer Form. Zu Günter Grass’ Roman Ein weites Feld. Berlin: Weidler 2008. 310 S. Bd. 168: Svoboda Dimitrova-Moeck: Women Travel Abroad 1925-1932: Maria Leitner, Erika Mann, Marieluise Fleisser, and Elly Beinhorn. Women’s Travel Writing from the Weimar Republic. Berlin: Weidler 2009. 283 S. Bd. 169: Gregory A. Knott: Arnold Stadler: Heimat and Metaphysics. Berlin: Weidler 2009, 212 S. Bd. 170: Christian Frankenfeld: “Über jede Liebe kommt das Gesetz”. Zum Utopieschwund im Werk Thomas Braschs. Berlin: Weidler 2011. 348 S. Bd. 171: Angela Kölling: Writing on the Loose. Reading Florian Illies’s Generation Golf, Maurice G. Dantec’s Périphériques, Joschka Fischer’s Mein langer Lauf zu mir selbst, and Frédéric Beigbeder’s Windows on the World as examples of creative nonfiction. Berlin: Weidler 2012. 248 S. Bd. 172: Thorbjörn Ferber: Nationaler Antisemitismus im literarischen Realismus. Berlin: Weidler 2014. 467 S. Bd. 173: Ivo Theele: Frauen│gestalten. Inszenierte Weiblichkeit in Rainer Maria Rilkes Frühwerk. Berlin: Weidler 2015. 361 S. Bd. 174: Elias Flügge: Zimmer, Raum, Räumungen. Zur Positionierung weiblicher Figuren im ‚Privatraum‘ bei Autorinnen des 20. und 21. Jahrhunderts. Berlin: Weidler 2016. 295 S.

Revised Use Case Point Method - Effort Estimation in Development Projects for Business Applications - Frohnhoff, Stephan; Engels, Gregor (Setting Quality Standards, Proceedings of the 11th International Conference on Quality Engineering in Software Technology (CONQUEST 2008), Potsdam (Germany))
Rapid and precise effort estimation of software development projects is crucial in IT industry. In a case study, the Use Case Point (UCP) method was applied to 15 commercial software development projects. The estimated efforts were compared with the incurred project efforts. We measured a standard deviation of 42 %. This is not acceptable for industrial usage. Therefore, we propose appropriate improvements of the Use Case Point method leading to significantly higher estimation accuracy with only 20 % standard deviation. The contribution of this paper is a detailed description of the improved Use Case Point method.

Logik, Mathesis universalis und allgemeine Wissenschaft. Leibniz und die Wiederentdeckung der formalen Logik im 19. Jahrhundert - Peckhaus, Volker
Rezensionen: J. Legris, “Mathesis Universalis”, Mathesis 13 (1997), 167– 175; Zbl. Math. 884.01021 (R. Murawski); Philosophischer Literaturanzeiger 51 (1998), 114–117 (G. Schenk); MR 98h:01013 (H. Sinaceur); Peirce Project Newsletter 3 No. 1, 7; Philosophiegeschichte und logische Analyse. Logical Analysis and History of Philosophy, Bd. 2, Mentis: Paderborn 1999, 259–264 (W. Malzkorn); History and Philosophy of Logic 20 (1999), 67–69 (H. Linneweber-Lammerskitten); Erkenntnis 50 (1999), 133–136 (P. Mancosu); Berichte zur Wissenschaftsgeschichte 22 (1999), 207–208 (P. Mancosu); NTM. Schriftenreihe für Geschichte der Naturwissenschaften, Technik und Medizin N.S. 8 (2000), H. 1, 290 (K.-H. Schlote), 49–50; Anuario Filosofico 32 (1999), 853–854; M.F., “La logica di Leibniz nel XIX secolo”, Giornale critico della filosofia Italiana 6 ser. 20 (2000), 161–164; Archiv für Geschichte der Philosophie 82 (2000), 349–352 (R. Vilkko); Epistemologia 24 (2001), 152–155 (M. Ferriani); The Review of Modern Logic 9, nos. 3 & 4 (2003–2004), 119–122 (H. Frank).